The Role of the Prayer Room as a Community Religious Activity (Study on the Al-Mutmainah Prayer Room in Singaraja Village, Indramayu) - M. Fhalikh Mubarok (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2025)
This study aims to determine the role of the prayer room (Musholla) as a community religious activity (a study of the Al-Mutmainah prayer room in Singaraja Village, Indramayu). The research methodology used in this article is qualitative research aimed at understanding the phenomena experienced by the research subjects, including explaining behavior, perceptions, and motivations in specific contexts using various natural methods. Data collection techniques included in-depth interviews, participant observation, and documentation, with data validation through triangulation. The results indicate that the success of the Al-Mutmainah prayer room is supported by a spirit of sincerity in its management and the participation of its residents. All activities are funded by voluntary donations, with no mandatory fees burdening the congregation. The Quran teachers and caretakers work voluntarily, without fixed compensation, as a form of devotion to religion and the community. This sincerity fosters trust and a sense of collective responsibility among residents.